The Implementation of the RADEC Learning Model through the WhatsApp Application to Increase the Creativity of Elementary School Students - Rosyidi, Ahmad; Muharam, Agus; Sujana, Atep (International Conference on Elementary Education, 2022)
The application of innovative learning models is one of the things that plays an important role in the progress and improvement of the quality of education in schools. This research was conducted by applying the read-answer-discuss-explain-create (RADEC) learning model in locomotor material. The purpose of this study was to determine students' creativity in locomotor materials through the application of the RADEC learning model in grade 5 elementary schools. This application research becomes more challenging with the use of various online (online) applications as media in the implementation of face-to-face substitute learning in classrooms during the COVID-19 pandemic. The subjects in this study were 24 5th grade students of Karyamukti State Elementary School, Cibatu District, Garut Regency, consisting of 11 females and 13 males. This study uses a descriptive method with a qualitative approach. Data collection is done by using question instruments and collecting student works in learning. The results of this study indicate that the RADEC learning model helps students increase creativity in learning and produce creative and innovative works after participating in learning.